2009
DOI: 10.1177/0734282909344416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parental Education Level on Fluid Intelligence of Philippine Public School Students

Abstract: This study examines the effect of parental education levels (PELs) on the fluid intelligence of Filipino public school students. The data were drawn from a normative study of a nonverbal intelligence test involving more than 2,700 students sampled across the country. As expected, PELs have a significant impact on fluid intelligence as measured through a nonverbal intelligence test. The results indicate that PELs account for an increase of roughly three IQ points for every increment in PEL. Students with colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
2
7
0
2
Order By: Relevance
“…Step Consistent with previous research (e.g., Vista and Grantham 2010), findings of the present study indicate that higher family SES is associated with higher levels of school achievement for children. Indeed, higher income and highly educated parents can enhance their children's school achievement by providing their children an array of services and goods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Step Consistent with previous research (e.g., Vista and Grantham 2010), findings of the present study indicate that higher family SES is associated with higher levels of school achievement for children. Indeed, higher income and highly educated parents can enhance their children's school achievement by providing their children an array of services and goods.…”
Section: Discussionsupporting
confidence: 91%
“…To date, there has been a dearth of research on the impact of parental expectations and parental beliefs on parenting style. Numerous studies have demonstrated that family socioeconomic status (SES) indicators, such as family income and parental education, are associated with school achievement (see Bradley and Corwyn 2002;Sirin 2005;Marks et al 2006;Vista and Grantham 2010) and parental involvement (e.g., Chao and Willms 2000;DeGarmo et al 1999;Grolnick et al 1997;Jeynes 2010a). Therefore, family SES was included in the study as a control variable.…”
Section: Parenting Style and School Achievementmentioning
confidence: 99%
“…Third, because we operationalized GMA with BTACT, which emphasized the information‐processing component of intelligence (i.e., fluid intelligence; see Stawski et al., ), it was unclear whether our model would hold when GMA was measured with crystallized intelligence, which represents the accumulation of specific knowledge in one or more disciplines (Ackerman, ; Cattell, ). Because MIDUS II did not contain explicit measures of crystalized ability (e.g., vocabulary, verbal reasoning, numerical reasoning; Postlethwaite, ), we used level of education as a proxy (Moran, ; Stawski et al., ; Vista & Grantham, ). In the data set, education was coded as a continuous variable with 12 possible values (1 = no school/some grade school; 12 = PhD, EdD, MD, DDS, LLB, LLD, JD, or other professional degree).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are in accord with recent findings in this area, namely that of Gur et al (2010) whose findings suggest that higher parental education is associated with better performance across domains within executive functioning, on the same neuropsychological test battery. Furthermore, in a study on Philippine students who had diverse socio-demographic backgrounds, Vista and Grantham (2010) found that parental education had a significant influence on fluid intelligence. Lawlor, Najman, Batty, O'Callaghan, Williams, and Bor (2006) in their study, via multivariable analyses, contend that among the strongest and most robust predictors of intelligence are family income, parental education and education, with these and other variables explaining 7.5% of the variation in intelligence at age 14.…”
Section: Discussionmentioning
confidence: 98%